Pengaruh Rasio Keuangan Pada Pertumbuhan Laba Perusahaan Tambang Yang Tercatat Dalam Bursa Efek Indonesia Pada Periode 2018-2021 - Mustamu, Mercy Anastasia; R Nasution (ITB AAS INDONESIA, 2025)
The objective of this research is to determine the effect of the financial ratio on the profit growth of the mining companies that are listed on the Indonesia Stock Exchange from 2018 to 2021. The financial ratios that are the variables for this study are the profitability ratios, which are focused on Return on Assets (ROA) and Return on Equity (ROE); the liquidity ratios, which are focused on Current Ratio (CR); and the activity ratios, which are focused on Total Asset Turnover (TATO). A judgment sampling technique was employed to select a representative sample of 13 companies. The collected data was analyzed using multiple linear regression analysis with the IBM SPSS v26 statistical program. The result of the research indicates that ROA, TATO, and CR have a significant influence on profit growth. While ROE has no significant effect on profit growth of the mining companies.